Math, asked by MrSmartGuy1729, 11 months ago

The ratio of the sum of first m and n terms of an Ap is m^2:n^2.show that the ratio of its nth and nth term is (2m-1):(2n-1)​
Good answer will be marked as the Brainliest

Answers

Answered by BrainlyPopularman
6

GIVEN :

The ratio of the sum of first m and n terms of an Ap is m² : n².

TO PROVE :

The ratio of its mth and nth term is (2m-1):(2n-1).

SOLUTION :

• We know that Sum of an A.P. is –

  \\ \dashrightarrow \large{ \boxed { \bold{S_{n}  =  \dfrac{n}{2} \{2a + (n - 1)d \}}}} \\

• Here –

  \\ \:  \:  {\huge{.}} \:  \: { \bold{a = first \:  \: term}} \\

  \\ \:  \:  {\huge{.}} \:  \: { \bold{d = common \:  \: difference}} \\

• According to the question –

  \\ \implies { \bold{ \dfrac{S_{m}}{S_{n}}  =  \dfrac{m^2}{n^2}}} \\

  \\ \implies { \bold{ \dfrac{\dfrac{m}{2} \{2a + (m - 1)d \}}{\dfrac{n}{2} \{2a + (n - 1)d \}}  =  \dfrac{ {m}^{2} }{ {n}^{2} }}} \\

  \\ \implies { \bold{ \dfrac{2a + (m - 1)d}{2a + (n - 1)d}  =  \dfrac{m}{n}}} \\

  \\ \implies { \bold{ {n(2a + md - d)} = {m(2a +nd - d)}}} \\

  \\ \implies { \bold{2an + mnd - nd = 2am + mnd - md}} \\

  \\ \implies { \bold{2an - nd = 2am  - md}} \\

  \\ \implies { \bold{2an - 2am = nd - md}} \\

  \\ \implies { \bold{2a(n -m) = d(n - m)}} \\

  \\ \implies { \bold{2a= d \:  \:  \:  \:  -  -  -  - eq.(1)}} \\

• We know that nth term –

  \\ \dashrightarrow \large{ \boxed { \bold{T_{n}  = a + (n - 1)d }}} \\

  \\ \implies  { \bold{ \dfrac{T_{m}}{T_{n}}  = \dfrac{a + (m- 1)d}{a + (n - 1)d}}} \\

• Using eq.(1) –

  \\ \implies  { \bold{ \dfrac{T_{m}}{T_{n}}  = \dfrac{a + (m- 1)2a}{a + (n - 1)2a}}} \\

  \\ \implies  { \bold{ \dfrac{T_{m}}{T_{n}}  = \dfrac{a \{1+ (m- 1)2 \}}{a  \{1+ (n - 1)2 \}}}} \\

  \\ \implies  { \bold{ \dfrac{T_{m}}{T_{n}}  = \dfrac{1+ (m- 1)2} {1+ (n - 1)2 }}} \\

  \\ \implies  { \bold{ \dfrac{T_{m}}{T_{n}}  = \dfrac{1+2m - 2} {1+2n - 2 }}} \\

  \\ \implies \large {\boxed{  { \bold{ \dfrac{T_{m}}{T_{n}}  = \dfrac{2m -1} {2n -1}}}}} \\

  \\ \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \large {\boxed{{  \underline{ \bold{Hence \:  \: proved }}}}} \\

Similar questions